THE ROLE OF JOURNALIST IN COVID VACCINES 19 PERSUASIVE ADS: PERAN JURNALIS DALAM IKLAN PERSUASIF TERHADAP COVID-19 - Zahro, Ami Fatimtuz; Abdurrohim Ali; Raodatuljannah (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2021)
The purpose of this study was to find out the role of journalists in the Covid-19 pandemic and find out how to identify hoax news spread, especially on social media. This research object is a secondary research object, where the material used to earn data income in the form of written documents such as journals, articles and written news. The method that researchers use is observation list, where the author collects data through some existing written data to review and prove the truth of the research conducted. In this article researchers prove that a journalist is considered the most important role in delivering news accurately and vaktually. News is also spread through social media so that the public avoids hoax news that is easily spread in the general public. Hoax news is news that is uncertain or does not have the truth in the content of the news, for that as a society, as a society.